A review of sideline assessment measures for identifying sports-related concussion. (June 2018) - Albicini, Michelle; McKinlay, Audrey
Currently, there is a lack of clear, "gold standard" guidelines for the identification and management of sports-related concussion. This is of concern considering the importance of preventing further injury during game-play. Moreover, a number of assessment measures and tools aim to detect concussion in athletes and help inform return to play decisions, including the assessment of posture and balance, eye-saccades, memory, attention, orientation and post-concussive symptomatology. However, they have often not been widely disseminated for validity studies, and their utility or sensitivity in detecting concussion is limited due to a number of factors. As such, this review will examine current guidelines and sideline assessments measures which aim to inform decisions about return to play following sports-related concussion.